Aerosol science : technology and applications - Colbeck, I. (Ian); Lazaridis, Mihalis (West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
Reviewing many technological applications together with the current scientific status of aerosol modelling and measurements, this book includes: Satellite aerosol remote sensing; The effects of aerosols on climate change; Air pollution and health; Pharmaceutical aerosols and pulmonary drug delivery; Bioaerosols and hospital infections; Particle emissions from vehicles; The safety of emerging nanomaterials; Radioactive aerosols: tracers of atmospheric processes. With the importance of this topic brought to the public's attention after the eruption of the Icelandic volcano Eyjafjallajökull, this book provides a timely, concise and accessible overview of the many facets of aerosol science. --
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Aerosols -- Industrial applications; Aerosols -- Environmental aspects; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Electronic books; Electronic books